Overparenting pada anak usia dini dan dampaknya terhadap kemandirian anak - Salsabila, Naisa Assyfa (Maliki Interdisciplinary Journal, 2026)
This study aims to critically examine the phenomenon of overparenting in early childhood and its implications for children's independence development. Overparenting is not merely defined as high parental involvement, but rather as excessive control that limits children's opportunities to learn through direct experience.This research employs a qualitative descriptive approach using a literature review method, drawing on various relevant academic sources such as scientific journals, books, and scholarly publications. The findings indicate that overparenting significantly contributes to the inhibition of children's independence, affecting behavioral, emotional, and cognitive aspects. Children raised under this parenting style tend to develop higher dependency, lower self-confidence, and limited problem-solving abilities.Furthermore, overparenting also impacts children's social and emotional development, including increased anxiety and difficulties in adapting to new environments. These conditions arise due to the lack of opportunities for children to explore, make decisions, and learn from failure independentlyTherefore, this study emphasizes the importance of implementing a balanced parenting approach that integrates guidance and autonomy. Providing children with appropriate freedom according to their developmental stage is essential in fostering independence and preparing them to face future life challenges.